Atendimento bancário na pandemia de Covid-19: percepção de bancários e de clientes diante da transformação digital - Rodrigues, Paulo Henrique (2021)
The Covid-19 pandemic imposed a series of restrictions on mobility and changes in the daily lives of the world population, accelerating the digital transformation in banking services, with the expansion of the digital channel (from brick to click). However, as the pandemic is controlled and commercial activities are resumed, bank branches will be reopened for service and, in this situation, customers will have the option of returning to the face-to-face channel for service. The main objective of this study was to analyze the perception of bank employees and customers regarding the digital transformation that occurred in banking services during the Covid-19 pandemic. A survey was carried out with customers (431 respondents) and bank employees (719 respondents) and, from the qualitative analysis, it was possible to see a change in the way banks work, where most bank employees worked remotely at some point during the Covid-19 pandemic, enabling an increase in the offer by banks of banking services through digital channels in this period. This increase in offer was noticed by customers, who indicated a change in their behavior with the increase in the use of digital channels for service during the pandemic and pointed out that the ease of use of these channels, followed by the restriction in face-to-face service imposed by the pandemic, were the main reasons for this increase. In the perception of bank employees and customers, this change that occurred with the digital transformation in banking services will be sustained after the Covid-19 pandemic.